Dual phase statistical optimization of biological pre-treatment of sugarcane bagasse with Pycnoporus coccineus MScMS1 for polyhydroxyalkanoates production. (15th January 2022) - de Souza, Larissa; Shivakumar, Srividya; Das, Arijit
Abstract: Biological pre-treatment is the removal of recalcitrant lignin from lignocellulose through the action of lignin degrading organisms and/or their ligninolytic enzymes system. Despite numerous environmental benefits, biological pre-treatment has been side-lined due to its prolonged periods of fermentation, ascribed to the slow growth rate of lignin degrading organisms. Thus, the present work adopted a dual phase statistical optimization approach for the biological pre-treatment of sugarcane bagasse, with Pycnoporus coccineus MScMS1, using Taguchi Orthogonal Array, in conjunction with Response Surface Methodology, to address this issue. Amplification of the organism's functioning resulted in an enhancement of sugar productivity and yield accompanied by a significant reduction in fermentation time. Optimized sugar concentration was approx. 18 g/L within 4 days of pre-treatment, with productivity of 4.5 g/(L.day). Substrate compositional analysis revealed significant ( p < 0.05) reduction of lignin by 70% in the biologically pre-treated substrate, along with significantly ( p < 0.05) higher quantities of water soluble components (35 ± 0.95 g) and cellulose content (33 ± 0.18 g), as compared to the untreated substrate. Appreciable levels of xylose, arabinose, glucose and galactose were detected in hydrolysates from biologically pre-treated bagasse. Furthermore, Bacillus megaterium Ti3, a potent polyhydroxyalkanoates (PHA) producer, was grown on these sugar-rich hydrolysates and generated 0.58 g/L PHA in 24 h of fermentation accompanied by 0.88 g/L dry cell weight and 65% PHA accumulation. These results were comparable with those from a glucose medium. Thus, the present study was successful in optimizing the biological pre-treatment of sugarcane bagasse and utilizing the resultant sugar-rich hydrolysates, as inexpensive and renewable raw materials, for PHA production. Highlights: Statistical optimization with Taguchi Orthogonal Array & Response Surface Methodology. Optimized biological pre-treatment with organism yielded 18 mg/mL sugars in 4 days. Biological pre-treatment significantly ( p < 0.05) decreased lignin content by over 70%. PHA production from sugar-rich hydrolysates with 65% PHA accumulation in 24 h. Environment-safe biological pre-treatment yields renewable sugars for PHA production.